The Role of Digital Tools in Assessment and Their Impact on Educational Practices - Josephine Obiageli Okafor (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: The rapid advancement of technology in the 21st century has significantly influenced various aspects of education, particularly in assessment practices. Traditional assessment methods, often limited by time and scope, are increasingly being supplemented or even replaced by innovative digital tools that offer greater flexibility, accessibility, and interactivity. Objective: This study explores the role of digital tools in assessment and their impact on educational practices, focusing on how they transform traditional methods and enhance learning outcomes. Method: The study examines key technologies such as LMS, online quizzes, e-portfolios, and AI, emphasizing their role in personalized learning, real-time feedback, and data-driven decision-making. Result: Digital tools improve efficiency and student engagement while reshaping assessment practices, shifting from summative to formative approaches, and fostering collaboration among educators, administrators, and EdTech developers. Conclusion: While digital tools offer numerous benefits, challenges such as equity, data privacy, and technology dependence must be addressed. The responsible use of these tools is crucial for maximizing positive outcomes. Contribution: This study provides insights into the evolving landscape of digital assessment, highlighting future trends such as AI, gamification, and blockchain, and their potential to further transform education.